From Tissue to Transcriptome: A Robust Pipeline for Single-Cell RNA-seq of Primary Porcine Hepatocytes - Sharma, Prarthana (Translational Research in Veterinary Science, 2025)
The technical execution of single-cell RNA sequencing (scRNA-seq) in liver tissue poses notable challenges due to the inherent fragility of hepatocytes, the distinct metabolic zonation, and the rapid activation of stress-response mechanisms during tissue dissociation. These complications are further exacerbated in porcine liver, where the large size of hepatocytes and elevated endogenous RNase activity resemble human hepatic tissue, yet are particularly vulnerable to mechanical and enzymatic stresses. Conventional scRNA-seq methodologies frequently yield diminished cell viability, RNA degradation, and skewed representation of hepatic subpopulations when applied to porcine models. We introduce a reproducible and species-optimized protocol for conducting scRNA-seq on porcine liver. This methodology incorporates cold-active enzymatic dissociation, low-shear mechanical manipulation, RNase suppression, and debris-minimized density separation to maintain cellular integrity and transcriptomic accuracy. A brief in vitro stabilization phase further improves cell viability and mitigates ambient RNA contamination, yielding single-cell suspensions amenable to droplet-based systems, such as the 10× Genomics v3.1 and v4 chemistries. Benchmarking outcomes reveal high viability rates (>80%), substantial transcript complexity, and consistent recovery of both parenchymal and non-parenchymal populations with diminished stress-response profiles. This workflow establishes a standardized approach for high-fidelity, cross-institutional scRNA-seq investigations and bolsters translational research applications in toxicology, pharmacokinetics, and hepatoprotective therapies. Acknowledgement This research is financed and supported by the scientific project NCN-OPUSLAP (UMO-2021/43/I/NZ9/02612) entitled: Multilevel molecular analysis of the hepatoprotective effect of medicinal herbs extracts in prevention of liver dysfunction caused by aflatoxin B1 in pig as an animal model (in-vivo), and hepatocyte cell culture analysis in human and pig (in-vitro).